Estimating the production function for human capital: Results from a randomized controlled trial in Colombia - Orazio P. Attanasio; Sarah Cattan; Emla Fitzsimons; Costas Meghir; Marta Rubio-Codina (Institute for Fiscal Studies (IFS), 2020)
We examine the channels through which a randomized early childhood intervention in Colombia led to significant gains in cognitive and socio-emotional skills among a sample of disavantaged children aged 12 to 24 months at baseline. We estimate the determinants of parents' material and time investments in these children and evaluate the impact of the treatment on such investments. We then estimate the production functions for cognitive and socio-emotional skills. The effects of the program can be explained by increases in parental investments, emphasizing the importance of parenting interventions at an early age.
Keywords: H31; I24; I25; I28; I3; J38; O1; O15; O54; 330; Frühkindliche Bildung; Kognition; Soziales Verhalten; Produktionsfunktion; Bildungsinvestition; Theorie; Kolumbien